Case Report: Anaphylactic shock induced by cefoperazone sodium and sulbactam sodium for injection - Liu, Weiqian; Gao, Bo; Xie, Shaowei; Yan, Dongrui; Yin, Yu (Frontiers in Medicine, 2025)
RationaleCefoperazone-sulbactam is a widely used antibiotic in clinical practice, and anaphylactic shock is a severe adverse drug reaction. Previous literature has rarely reported cases of anaphylactic shock induced by cefoperazone-sulbactam.Patient concernsA 38-year-old male patient who underwent surgery for cerebral hemorrhage developed fever, with considerations of pulmonary and urinary tract infections. Following the administration of injectable cefoperazone-sulbactam, he experienced anaphylactic shock.DiagnosisAnaphylactic shock was suspected to be caused by injectable cefoperazone-sulbactam.InterventionsThe patient was administered a subcutaneous injection of 1 mg epinephrine, followed by continuous infusion of 10 mg norepinephrine in 45 mL of 5% glucose solution via a pump. Additionally, assisted ventilation with a respirator and fluid resuscitation were provided.OutcomeThe patient was discharged with improved symptoms.LessonsTo prevent serious adverse reactions, it is essential to strictly adhere to indications and contraindications to avoid misuse and minimize the occurrence of adverse effects. Prior to medication administration, a thorough inquiry into the patient’s drug allergy history and family history should be conducted.